Effect of nutritious snacks provision on breakfast adequacy and nutritional status of elementary school students - Salwa Inayah Huda MA Parewasi; Hardinsyah Hardinsyah; Ikeu Ekayanti (Journal of Health and Nutrition Research, 2026)
Inadequate breakfast intake and malnutrition remain significant public health concerns among school-aged children in Indonesia, particularly in regions with a high Prevalence of Undernourishment (PoU). To address this, the National Food Agency (BAPANAS) implemented the GENIUS program (Gerakan Edukasi dan Pemberian Pangan Bergizi untuk Siswa), which integrates nutrition education with the provision of standardized nutritious snacks. This study aims to analyze the impact of the GENIUS program on breakfast adequacy and nutritional status among elementary school students in ten Indonesian provinces with PoU exceeding 5%. A pre-experimental pre–post study design was employed, involving 4,953 students in grades 4-6. The intervention consisted of 20 nutrition education sessions and the daily provision of standardized snacks (250–300 kcal per serving) and UHT milk over a two-month period. Breakfast adequacy was assessed using 24-hour breakfast recalls. Snack compliance was also monitored daily. The intervention led to significant improvements in breakfast nutrient intake (p < 0.05). Mean energy intake increased from 141.9 kcal to 393.5 kcal, protein from 4.0 g to 11.5 g, fat from 5.6 g to 14.9 g, and carbohydrates from 17.7 g to 48.9 g. Substantial gains were also observed for key micronutrients, including calcium, phosphorus, and iron . Despite these dietary improvements, BMI-for-age z-scores showed no meaningful change (-0.2 ± 1.4 at baseline vs. -0.2 ± 1.5 at endline), consistent with the short duration of the intervention. Snack compliance was notably high, with 93.5% of students achieving high adherence (≥70%). The GENIUS program effectively enhanced the quality and adequacy of breakfast among students in food-insecure regions. While the two-month duration was sufficient to improve nutrient intake, it was inadequate to produce measurable changes in nutritional status. Future programs should consider longer implementation periods and strengthened school-family engagement to support sustained improvements in growth outcomes